OP0094 Steady-state plasma concentrations of rofecoxib in children with juvenile rheumatoid arthritis. (1st June 2001) - Truitt, KE; Ferrandiz, M; Kiss, M; Forre, OT; Porras, AG; Wong, P; Rose, E St.; DeTora, LM
Abstract : Background: Objectives: To compare the steady-state AUC(0–24 h) of rofecoxib, dosed @ approx 0.32 mg/kg/day in children aged 2 to 17 years vs. adult historical controls who received one 25-mg tablet daily (mean weight of 77.7 kg, corresponding to 0.32 mg/kg/day). Methods: Two trials were performed. In one, adolescent JRA patients (12 to 17 years) received 12.5 mg or 25 mg tablets to approximate 0.32 mg/kg/day. In another, JRA patients aged 2–11 years received rofecoxib 2.5 mg/ml suspension to approx. 0.32 mg/kg/day. Both formulations have equivalent bioavailability. All patients received once-daily rofecoxib for at least 8 days (to presumptive steady state) then trough and post-dose blood samples were obtained for up to 24 h. To minimise the number of blood samples for 2–5 year-olds, 2 sampling schedules with different time points were used. Comparison to adult historical controls was made by calculating AUC(0–24 hr) geometric mean ratio (GMR) with corresponding 90% confidence intervals (CI) for specific paediatric age groups: 12–17 yrs; 6–11 yrs; and 2–5 yrs; relative to adult controls. Similar comparisons were made for Cmax. Summary statistics for AUC(0–24 hr) were calculated for each treatment (12.5 mg or 25 mg Rofecoxib) in patients 12–17 years. Results: See Table 1 . 12–17 yr-old patients taking 12.5 mg or 25 mg rofecoxib showed similar exposure to adult controls receiving the same dose. Rofecoxib was generally well-tolerated in all patients and age ranges studied. Conclusion: Based on these results, children aged 2–11 yrs require a higher mg/kg/day dose of rofecoxib for similar steady-state systemic exposure to adult historical controls receiving 25 mg. Assuming linear dose proportionality, a dose of 0.6 mg/kg/day in children aged 2–11 yrs, should approximate the exposure of 25 mg in adults and adolescents aged 12–17 yrs showed similar systemic exposure to adults taking identical doses of rofecoxib. Funded by a grant from Merck and Co., Inc.